Community based rehabilitation by paraplegic - a case report - Lanke, Ravindra S.; Dudhekar, Ulhas J.; Mote, Girish B.; Badole, Chandrashekhar M. (International Journal of Research in Medical Sciences, 2017)
A journey of a young man started from day one in the hospital. When he came with the traumatic paraplegia, no doubt a paraplegic has to face a lot of challenges in his life when he came to know that his both legs are not working. He became bedridden and his moral is also become down for his future planning. But we accept the challenge, a team work by an orthopaedician and a physio-occupational therapist make it little easier. Postoperatively we prefer to offer rehabilitation through community base programme. Inspiration of hospital environment and equipment are going to help him for such kind of programme he accepts the challenge, basic aim of providing this programme is to reduce duration as well as incurred monitor losses. Special attraction of this case report is homemade bicycle, which served the purpose of providing repetitive rhythmic mobilisation of bilateral lower limbs which facilitates normal pattern of ambulation. Now he is ambulatory and goes back to his work. So, a person with spinal cord injury involved with their community with a little modification in his activity and equipment is worth for him. Traumatic paraplegia offers a big challenge to physio- occupational therapist due to long term recovery it takes. For Such patients on regular follow up till complete recovery, we preferred community based rehabilitation. This made him independent and incurred reduced monitory losses.